Antara Relativisme dan Ikhtilaf dalam Tafsir Al-Qur’an: Sebuah Kajian Perbandingan Kritis: Between Relativism and Ikhtilaf in Qur'anic Interpretation: A Critical Comparative Study - Lalu Heri Aprizal (Center of Islamic and Occidental Studies, 2025)
The liberal approach to Qur'anic interpretation affects the framework of Muslims toward their religion. This perspective requires that what was produced by previous scholars of tafsir is considered relative. It then deconstructs all established religious interpretations, and leads to the anti-authority movement, so that no one can know the meaning of the Qur'anic verses except the absolute God. This argument seems to be supported by the fact that scholars sometimes differ in their opinions in interpreting Qur'anic verses. The problem is, are the differences in scholars' interpretations a form of relativism? This article aimed to show the significant difference between relativism in tafsir, which denied the truth of religious interpretations, and ikhtilaf tafsir, which was a difference in the interpretations of scholars. This paper is qualitative in nature using the library research method. The data collected have been described and critically analyzed, especially those related to relativism in and ikhtilaf tafsir. From there, the author then conducted a comparative study to find the differences between the two. The author found that relativism in tafsir is not the same as ikhtilaf tafsir. Ikhtilaf tafsir can be discussed scientifically to reach the best interpretation, while relativism in tafsir tends to aim to reject and deconstruct the interpretations of the scholars, then replace them with new interpretations that are considered more in line with the times.